1998
DOI: 10.1073/pnas.95.7.3621
|View full text |Cite
|
Sign up to set email alerts
|

The expression of matrix metalloproteinase 9 is enhanced by Epstein–Barr virus latent membrane protein 1

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
202
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 210 publications
(216 citation statements)
references
References 58 publications
(60 reference statements)
13
202
0
1
Order By: Relevance
“…[13][14][15] MMP1 should contribute to tumor progression in NPC by means of its ability to destroy interstitial collagens.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] MMP1 should contribute to tumor progression in NPC by means of its ability to destroy interstitial collagens.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported that LMP1 stimulated expression of matrix metalloproteinase-9 (MMP-9), which is implicated in tumor invasion and metastasis by degrading type IV collagen, a major component of basement membrane (Yoshizaki et al, 1998;Takeshita et al, 1999). Expression of MMP-9 gene was at a very high level in parental MDCK cells and was not further stimulated by transformation with LMP1 (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…When the authors could not find any vessel structure highlighted in the tumor stroma, the specimen was considered A pcDNA3-based LMP1-expression plasmid (pcLMP1) has been described previously [23] . Ad-AH cells are an EBV-negative human nasopharyngeal epithelial cell line [24] .…”
Section: Introductionmentioning
confidence: 99%